Evaluación fotoquímica, actividad antimicrobiana y letal del tubérculo Eriotheca SP con potencial farmacológico. - Pineda Ojeda, Xavier Andrés (2015)
The works that harmonize chemical and bilógicos studies are an important part of the publications that are in the most important data bases. This paper addresses these trends and aims to assess the secondary metabolites, antimicrobial activity and tuber lethal Eriotheca sp To carry out this research, the dried and ground sample different parts of the tuber Eriotheca sp was obtained. A dry drug obtained is practiced analyzes residual moisture and total ash. The first given within recommended while the latter no values. They were then extracted with methanol and water. In both extracts they were determined pH, refractive index and density. The pH value obtained suggests the presence of phenolic compounds. The aqueous extract it is determined the% Brix, invert sugar, glucose and% fructose. The values obtained were higher for pulp. When she underwent methanol extract IR spectroscopy, a study of phytochemical screening assays, antibacterial and antifungal activity and lethality against Artemia salina. The results showed the presence of phenolic compounds and alkaloids, and deadly good antibacterial activity. The antifungal activity was low. From the crude methanol extract of alkaloids, which was analyzed by thin layer chromatography demonstrating diversity composition for each of the studied parts was obtained. From the results it is recommended to continue studies for determining the parameters of the drug quimicofísicos and extracts, deepen chemical and microbiological studies and evaluate the antitumor activity of the extracts.